2018
DOI: 10.1002/pbc.27540
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of vinblastine and temsirolimus in pediatric patients with recurrent or refractory solid tumors: Canadian Cancer Trials Group Study IND.218

Abstract: Combining mammalian target of rapamycin (mTOR) inhibitors and vinca alkaloids has shown therapeutic synergy in xenograft models of pediatric cancers. This phase I study assessed safety and toxicity of temsirolimus in combination with vinblastine in children. Procedure Patients ≥ 1 and ≤ 18 years with recurrent/refractory solid or CNS tumors were eligible. Vinblastine (4 mg/m2) and temsirolimus (15 mg/m2) were administered i.v. weekly, with planned dose escalation of vinblastine using a rolling six phase I desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…28 Hypercholesterolemia and hypertriglyceridemia are common in both adult and pediatric mTOR inhibitor studies, although in pediatric studies, this tends to be low grade and/or infrequent, and easily managed. [28][29][30][31] The results of this study are consistent with these data as only one patient had > grade 2 hypertriglyceridemia and no patient had > grade one hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…28 Hypercholesterolemia and hypertriglyceridemia are common in both adult and pediatric mTOR inhibitor studies, although in pediatric studies, this tends to be low grade and/or infrequent, and easily managed. [28][29][30][31] The results of this study are consistent with these data as only one patient had > grade 2 hypertriglyceridemia and no patient had > grade one hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the maximum grade of mucositis for all patients in subsequent cycles was grade 2 ( n = 2), suggesting this toxicity improves in subsequent cycles as reported in other studies . Hypercholesterolemia and hypertriglyceridemia are common in both adult and pediatric mTOR inhibitor studies, although in pediatric studies, this tends to be low grade and/or infrequent, and easily managed . The results of this study are consistent with these data as only one patient had > grade 2 hypertriglyceridemia and no patient had > grade one hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that this combination was well tolerated without severe toxicities, despite a heavily pretreated population. All toxicities were manageable and were already described when using each compound alone [14][15][16][17][18][19][20][21][40][41][42][43]. As in multiple phase I exploring targeted therapies, the MTD was not determined in absence of significant DLT events up to the tenth level (rapamycin at 2.5 mg/m 2 /day and D1/D15 irinotecan at 240 mg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that tumors, like neuroblastoma, rhabdomyosarcoma, high-grade glioma, or osteosarcoma, are overexpressing these targets and are sensitive to mTor inhibition [4,5,[12][13][14][15][16][17][18][19]. Therefore, rapamycin has been used in multiple phase I trials in these malignancies as single agent or in combination with chemotherapy [12][13][14][15][16][17][18][19][20][21]. The results of these protocols were promising, but they also showed limitations due to a positive feedback loop, reactivating constantly mTor through upstream RAS/mitogen-activated protein kinase (MAPK) pathway [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, compound 14a is still being used in the clinical practice and still undergoes various research trials. Most considered is its co-administration with other commonly used drugs, as seen, for example, in [ 147 ]. In 1963, another preparation containing vinca alkaloid 14b has entered the drug market, namely, Oncovin ® .…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%